COMPARATIVE PRELIMINARY PHYTOCHEMICAL STUDIES OF IN VIVO AND IN VITRO EXTRACTS OF GLORIOSA SUPERBA L. - RATHOD DIPIKA; PATEL ILLA (International Journal of Pharma and Bio Sciences, 2016)
Gloriosa superba L. (Liliaceae) is known for its valuable alkaloid content colchicine. It is highly used in traditional and modern therapies. Seeds and tubers of this plant contain medicinally potential alkaloid colchicine and have been traditionally used for treatment of ulcer, cancer, gout etc. The present study was done to screen various phytochemicals by using two different solvents viz. Water and Methanol. Methanolic and aqueous extracts of in vivo (seed, leaf, tuber) and in vitro (shoots, tuber) plant samples were used for preliminary phytochemical screening. The results revealed that both extracts contain all most all type of phytochemicals like Alkaloids, Glycosides, Steroids and Tannins, but the methanolic extracts of in vitro plant samples gave better results than other samples in aqueous system.